2005
DOI: 10.1016/j.rapm.2005.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Versus Single-Injection Lumbar Plexus Blocks: Comparison of the Effects on Morphine Use and Early Recovery After Total Knee Arthroplasty

Abstract: Postoperative infusion of local anesthetic around the lumbar plexus reduces morphine requirement and improves early recovery after total knee arthroplasty as compared with a single-injection block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…One study demonstrated a significant increase in obturator motor blockade at 6 hours postoperatively [33]. Urinary retention was registered in one trial [35], cardiac events in one [38] and hypotension in two [35, 37]. No significant differences between active and control groups were reported.…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated a significant increase in obturator motor blockade at 6 hours postoperatively [33]. Urinary retention was registered in one trial [35], cardiac events in one [38] and hypotension in two [35, 37]. No significant differences between active and control groups were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Femoral or posterior lumbar plexus infusions are well validated for hip [158, 187, 206, 207] and knee surgery in RCTs [208210] but might result in dangerous quadriceps femoris and hip adductor weakness if high doses of local anesthetic are administered to optimize analgesia [178]. Moreover, contrary to the brachial plexus, in the lower extremity a single perineural infusion will not cover all surgical sites as these are innervated by multiple nerves.…”
Section: Why Cpnb Instead Of Spnb?mentioning
confidence: 99%
“…A CLPB with a sciatic block decreased pain when compared to a PCA 34 and even was shown to be as effective as an epidural. 35 One study using ropivacaine did not show a difference in analgesia between a CLPB versus SSLPB when both were combined with a sciatic block, 36 although another study using levobupivacaine that also used a placebo infusion did demonstrate improved pain control with a CLPB versus SSLPB 37 (Table 1, References 38 and 39, regarding TKA but not included in the text).…”
Section: Resultsmentioning
confidence: 99%